Mass ratios of magnesium to calcium and phosphorus in the arteries of Japanese and Thai - Tohno Y. (2014)
To elucidate quantitative changes of Ca, P, and Mg in the arteries with aging, the authors investigated changes of the mass ratios of Mg to Ca and P in the arteries of Japanese and Thai by inductively coupled plasma-atomic emission spectrometry. The arteries of Japanese that were used were the thoracic and abdominal aortas, coronary, common iliac, internal iliac, external iliac, and femoral arteries, in which very high accumulations of Ca and P occurred in old age. The arteries of Thai that were used were the abdominal aorta, ramifying site of the abdominal aorta, coronary, common iliac, internal iliac, and external iliac arteries. It was found that there were extremely significant correlations both between Ca and Mg contents and between P and Mg contents in all of the arteries of the Japanese and the Thai. With regard to the mass ratio, the mass ratios of Mg to Ca ranged from 1.5% to 2.1% in the six arteries of the Japanese, except for the thoracic aorta at 3.1%, at an advanced stage of atherosclerosis, being similar to each other. In the arteries of the Thai, the mass ratios of Mg to Ca ranged from 1.9% to 3.0%, except for the coronary artery at 0.5%, at an advanced stage of atherosclerosis. The mass ratios of Mg to P ranged from 2.5% to 2.7% in the six arteries of the Japanese, except for the coronary artery at 1.8%, at an advanced stage of atherosclerosis. With regard to the arteries of the Thai, the mass ratios of Mg to P ranged from 1.9% to 3.3%, except for the coronary artery at 0.7%, at an advanced stage of atherosclerosis. These results revealed that both the mass ratios of Mg to Ca and Mg to P were almost similar among the arteries of Japanese and Thai, except for the coronary arteries. Therefore, these results suggested that the inorganic deposits in the coronary arteries of Japanese and Thai were similar to those in the intimal tunica of the thoracic aorta, whereas in the other arteries, they were similar to those in the middle tunica of the thoracic aorta.